(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2020)
The study investigates the Roman series «Biblioteca classica sacra» (1842-1848), in which nineteen ascetic and religious texts dating back to the 14th-17th centuries were published. Once the philological, historical, and cultural intentions of the publisher, Ottavio Gigli, are clarified, the Prose di Feo Belcari are analyzed and, in particular, the complex editorial story of the Vita del b. Giovanni Colombini is reconstructed.